1983
DOI: 10.1029/ja088ia01p00489
|View full text |Cite
|
Sign up to set email alerts
|

Method of remote sensing of horizontal stratification due to an ionospherically reflected powerful radio wave

Abstract: It is shown numerically that the group delay of a weak diagnostic radio wave is greatly reduced in the presence of a powerful radio wave of slightly lower frequency vertically incident on the ionosphere below the penetration frequency. The numerical results are qualitatively interpreted in terms of a narrow stop band for propagation in a spatially periodic medium, for wavelengths near twice the spatial period. Application to remote sensing of the horizontal density stratification in ionospheric modification ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Lapin and Tamoikin (1984) showed that the curvature of the periodic structure affects the probe-wave scattering only slightly if the distance between the height of the probe-wave scattering and pump reflection height is small compared with their distance from the receiver. These authors also concluded, in what appears to be work closely related to that of Fejer (1983), that the effect of a periodic lattice on the wave reflected from the F region can lead to attenuation. Lapin (1994) looked at the combined effects of ambipolar diffusion and turbulence on the relaxation time of the scattered waves from the E and D regions.…”
Section: Previous Workmentioning
confidence: 89%
See 2 more Smart Citations
“…Lapin and Tamoikin (1984) showed that the curvature of the periodic structure affects the probe-wave scattering only slightly if the distance between the height of the probe-wave scattering and pump reflection height is small compared with their distance from the receiver. These authors also concluded, in what appears to be work closely related to that of Fejer (1983), that the effect of a periodic lattice on the wave reflected from the F region can lead to attenuation. Lapin (1994) looked at the combined effects of ambipolar diffusion and turbulence on the relaxation time of the scattered waves from the E and D regions.…”
Section: Previous Workmentioning
confidence: 89%
“…There was a region of backscatter extending 10 km or more below the specular reflection height immediately after heater switch-off and which decayed, apparently moving upwards to the specular reflection level within about 100 ms. Perhaps this was an electron-density stratification in the Airy pattern of the standing HF wave which decayed. The large extent of more than 10 km below the reflection height may have been only an apparent one if the reduction in group delay for frequencies just slightly off the pump frequency really occurs as predicted by Fejer (1983). Although the probing wave was at the same frequency as the pump wave, the 60-s pulse length ensures that there is significant energy within a several-kHz bandwidth.…”
Section: F-region Echoesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we note that Fejer [1983] suggests a powerful diagnostic approach that could be used to measure absolute electron density perturbations associated with F region API. Because API gives rise to a spatially periodic medium, there is a substantial reduction in the group delay of probe waves having frequencies slightly greater than the modifying wave.…”
Section: Future Experimentsmentioning
confidence: 99%